Sikap afektif pensyarah maktab perguruan terhadap penggunaan komputer - Aliza, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 1998)
The purpose of this research is to study the relationship between attitudes in the affective domain , namely liking, confidence and anxiety towards computer utilization of lecturers in Teacher Training Colleges in the state of Johore. The instrument (Computer Attitude Scale- CAS) which was constructed by Lyod and Gressard (1 984) was used in this research. The research also examined the signzficant differences between computer utilization and some demographic factors such as age, gender. ownership of a computer, computer experience and number qf computer courses attended. A total of224 lecturers of teacher Paining Colleges in Johore particgated in this study. This study uses data analysis such as frequency, mean, t-test, One way Anova and Pearson Correlation 'r'. The finding indicated that respondents show positive attitudes towards computer utilization in leaching and learning. Iiowever, respondents' level of computer utilization is average. If was shown that respondent,^ use computer fi.equently for preparing exercises and exanzination questions (mean=3.18). The least usage was found in the Computer Assisted Instruction or Pengajaran Berbantukan Komputer ('BK) (mean=2.04). The result of the study also revealed that the 3 attitude sub scales (liking, confidence and anxiety) have a signzficant relationship towards computer utilization. The attitude sub scales which presented to have the strongest positive relationship was conjfidence (r=0.354) followed by liking (r= 0.285). Anxiety was found to be negatively related to eomputer utilization (r=-0.141).